ACHIEVEMENT GOAL ORIENTATION AND MATH ANXIETY AMONG UNIMAS UNDERGRADUATE STUDENTS - Low, Michele Yen Wen (Universiti Malaysia Sarawak (UNIMAS), 2020)
The purpose of present study was to investigate the relationship between achievement goal orientation and math anxiety. Different types of achievement goals (mastery goal, performance approach goal and performance avoidance goal) were explored in this study. Besides, the difference in math anxiety between gender was also explored. Questionnaire was chosen as our instrument to collect data and the sample of present study involved a total number of 400 UNIMAS undergraduate students. The questionnaire used in this study included Achievement Goal Questionnaire Revised (ACQ-R) and Math Anxiety Rating Scale (MARS). Quantitative and cross-sectional design was used in this study. Independent t-test was used to compare the difference in math anxiety between male and female and the Pearson’s correlation was used to determine the relationship between the achievement goal orientation and math anxiety. Present finding showed that in math anxiety between gender. Moreover, present finding proved that mastery goal had positive relationship with math anxiety and performance approach goal had negative relationship with math anxiety. Moreover, it also found that performance avoidance goal was not correlated with math anxiety.